RISK FACTORS FOR MATERNAL MORTALITY AT MUARADUA HOSPITAL, SOUTH OGAN KOMERING ULU, 2019–2023 - Alhamdi, Mochammad Haikal; Wiradhika, Ludy Diana; Fitri, Widya Jaya (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Maternal mortality is a key indicator of healthcare quality, reflecting disparities in access to care and the effectiveness of maternal health interventions. In South Ogan Komering Ulu, the maternal mortality rate has shown a concerning upward trend between 2019 and 2023. This study aims to identify the primary risk factors associated with maternal deaths at Muaradua Hospital and to provide practical recommendations for prevention. Researchers performed a descriptive cross-sectional analysis utilizing hospital records encompassing demographic, clinical, and socio-economic characteristics. A total of 13 maternal deaths were recorded during the study period. Hemorrhage emerged as the leading cause of death, followed by hypertension in pregnancy, infection, and other causes such as anesthetic complications, cardiac conditions, and respiratory disorders. Most deaths occurred during the post-partum period, particularly among women aged 20–33 and those in their first pregnancy. In conclusion, hemorrhage, hypertension, and post-partum complications were the main contributors to maternal mortality in this setting. Preventive efforts should focus on improving the quality of antenatal care services, ensuring the presence of skilled healthcare providers during childbirth, and strengthening the referral system to ensure timely and appropriate care.